Effectiveness and Efficiency of Regional Revenue And Expenditure Management In Kuningan Regency - Sudiana, Dodi; Marpuah Jamilah, Erni; Arifin, Zaenal; Firmansyah, Iman; Siswoyo, Mukarto; Nursahidin, Nursahidin (Green Publisher Indonesia, 2024)
The budget is a tool that encourages local government management to act economically, efficiently and effectively to achieve targeted goals. After the Covid-19 Pandemic, the Realization of Regional Revenue and Expenditure in Kuningan Regency every year has fluctuated, there has been a decrease and increase, especially in the period 2021 to 2023, even until there is a problem of payment delays. The government is an element in determining the direction of decision-making and determining the direction of government, so the government needs to implement good governance to create good governance, especially in the management of the APBD in order to realize the welfare of the community. The purpose of this study is to find out and analyze the effectiveness and efficiency of the Regional Revenue and Expenditure Budget of Kuningan Regency for the period of 2021 - 2023. The data was analyzed by a qualitative descriptive method with a phenomenological approach obtained values and indicators to measure the level of effectiveness and efficiency. The data sources used are primary and secondary data. The subject of this study is the measurement of regional revenue and expenditure performance, and the subject of this research is the variables for the implementation of the regional revenue and expenditure budget for 2021-2023. The results of the study show that (1) The development pattern of the level of effectiveness of the management of the Kuningan Regency APBD for the period of 2021 - 2023 tends to be stable. The results of the effectiveness analysis show that the average value of the effectiveness level of the management of the Kuningan Regency APBD for the 2021 - 2023 period of 93.53% is classified as Effective, and (2) The ability to manage the Kuningan Regency APBD for the 2021 - 2023 period is still inefficient, this is seen from the average value of the efficiency level of regional financial management which shows a result of 99.81% which is the criterion of Less Efficient.